Contribution of research training for meaningful learning - Mazo-Betancur, Lorena (2023)
Education provides the tools to develop critical thinking and problem-solving skills for the modern world. Meaningful learning is a reflection of knowledge construction driven by not only academic but also socio-affective processes, based on motivation, guidance, teamwork, and experiences that enrich university life. An important aspect of this is research training, as it provides students with a tool to develop projects and execute ideas by strengthening their abilities. It is necessary to highlight the importance of the teaching-learning process; recognize actors in the process; identify and strengthen investigative skills, attitudes, abilities, and competencies of both the teacher and the student; apply investigative methods oriented towards empirical and logical approaches; and finally, describe institutional conditions such as research groups or spaces, in order to emphasize the importance of the contribution of research training to meaningful learning.